The Study of Laterite Colour from Using Iron Ore Tailing Substitute Fine Aggregate - สิงห์เปา ศรันย์; ชูตระกูล ปลูกเกษม; ศิริลักษณ์ ศิวโรฒม์ (RMUTL Engineering Journal, 2019)
The main objective of this study was to utilise iron ore tailing from Phu-Ang source, Loei as a laterite colour. It was used to substitute the fine aggregate with -30+200 Mesh sieved size. It was found that the colour in CIE L*a*b* colour system was nearly identical to the natural laterite from Li source, Lamphun. With this, iron ore tailing could be replaced fine aggregate in the forms of a natural red colour as compared to a laterite colour. Besides, the labor cost could be saved, shortly white-wash time, and cheap material cost. However, the disadvantages were the high density mixture, ore resource distance, and the colour changing caused by the oxidized time in the ambient air